The Ambivalence of P. Ramlee: Penarek Beca and Bujang Lapok in Perspective - Barnard, Rohayati Paseng and Barnard, Timothy P. (Asian Cinema, 2002)
One of the great heroes of the Malay World is Hang Tuah, a fifteenth century Malay warrior in service to the ruler of Melaka. Hang Tuah traveled throughout Asia, and during these adventures he secured riches, concubines, and status for his patron through his multi-talented ability to fight, sing, dance, and create poetry. Hang Tuah became an icon, the archetypical Malay whose status was solidified in the recording of an epic tale that describes his adventures, the Hikayat Hang Tuah.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9hYy4xMy4yLjlfMQ